Pre-emptive Analgesia in Laparoscopic Cholecystectomy by Intraperitoneal Instillation of Bupivacain (Journal of Fatima Jinnah Medical University, 2018)
This study is designed to assess the efficacy of pre-emptive analgesic effect of bupivacain instillation in peritoneal cavity after laparoscopic cholecystectomy. Aims and Objective To evaluate the outcome of pre-emptive analgesia in laparoscopic cholecystectomy by Intraperitoneal instillation of Bupivacain in terms of incision site pain, Generalized abdominal pain and shoulder pain. Design and Duration: Prospective randomized study conducted from June, 2013 till May, 2015. Methods: This study includes 110 patients that were qualified for laparoscopic cholecystectomy. These patients were divided into two groups A & B. Selection in each group was at random. In Group A patients 20ml of plain normal saline was instilled into the peritoneal cavity after the procedure whereas Group B patients received 0.25% of bupivacain diluted to 20ml of normal saline. Skin and subcutaneous tissue and pre-peritoneal space was instilled with bupivacain after the induction of anesthesia and before the start of procedure. The indicators of the study were pain intensity in postoperative period, nausea and vomiting (PONV), shoulder pain and the analgesia request rate. The study is condacted in surgical Unit, III Sir Ganga Ram Hospital, Lahore. Results: The pain intensity and the post operative nausea and vomiting and shoulder pain were significantly less in the Group B compared to Group A patients. Conclusion: In patient undergoing laparoscopic cholecystectomy the instillation of bupivacain after the completion of the procedure is effective in attaining an adequate analgesia effect in post operative period.
Keywords: preemptive, bupivacaine, intraperitoneal, laparoscopic cholecystectomy, postoperative analgesia